Hydrodeoxygenation catalyst as well as preparation method and application thereof
By using acidic zeolite nanotube support and active bimetallic components catalysts, the problem of low efficiency and selectivity in the hydrodeoxygenation reaction of traditional zeolite molecular sieves is solved, and the preparation of cycloalkanes is achieved with high efficiency and good selectivity.
Patent Information
- Application Number
- CN202411978499.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The microporous structure of traditional zeolite molecular sieve limits the intra-crystal diffusion mass transfer of macromolecular reactants and intermediates, resulting in low efficiency and selectivity of hydrodeoxygenation reactions. At the same time, strong acidic sites are prone to lead to side reactions and carbon deposits.
Acid zeolite nanotubes are used as support and active bimetallic components (such as Ru and Co, Ni, Fe) are introduced on their surfaces, and they are calcined and reduced by preparative methods to form a catalyst with a high specific surface area and a uniformly connected micromesoporous structure.
The conversion rate of hydrodeoxygenation reaction and the selectivity of cycloalkanes are improved, the occurrence of side reactions and carbon deposits is reduced, the life of the catalyst is extended, and the preparation process of the catalyst is simplified.
Smart Images

Figure CN119771482A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of catalyst technology, and in particular to a hydrodeoxygenation catalyst, a preparation method thereof, and applications thereof. Background Art
[0002] With the development of the aerospace industry, the requirements for fuel performance in aircraft (such as airplanes, rockets, and missiles) continue to increase. Traditional petroleum-based jet fuels (aviation kerosene and rocket kerosene) are primarily composed of saturated paraffins, and their density and calorific value have reached their performance limits. The development of high-density hydrocarbon fuels based primarily on cycloalkanes and polycycloalkanes, with their advantages of high density and high volumetric calorific value, has attracted significant attention worldwide. The production of liquid aerospace fuels from biomass not only opens up new avenues for energy security but also provides an important path for the high-value utilization of biomass.
[0003] Lignin is the only naturally occurring aromatic hydrocarbon polymer. Natural reserves of lignin are vast, comprising 10-35% by weight of biomass, yet its energy density reaches as high as 40%. Lignin is inedible to humans, and its use does not negatively impact the food supply, eliminating the need for competition for food. Lignin depolymerization produces lignin-derived biomass, which contains high concentrations of phenolic monomers, dimers, and oligomers, making it an ideal raw material for the production of cycloalkanes. Using lignin-derived biomass as a raw material for hydrodeoxygenation to produce high-quality cycloalkanes is a promising approach for producing aerospace fuels.
[0004] Bifunctional catalysts possess both hydrogenation sites and deoxygenation sites, and can directly convert oxygenated compounds into hydrocarbon products. Zeolite molecular sieves have excellent shape selectivity, abundant acidic sites, good hydrothermal stability and thermal stability, and are the most widely studied catalyst carriers with excellent comprehensive catalytic performance. However, the limited micropores of zeolite molecular sieves limit the intracrystalline diffusion and mass transfer of macromolecular reactants and intermediates such as branched phenol monomers and dimers, and the longer mass transfer path may also lead to increased side reactions and catalyst deactivation. While the strong acidic sites of molecular sieves have deoxygenation capabilities, they also easily cause the deoxygenated intermediates to condense and form carbon deposits. Therefore, it is expected that the efficiency and selectivity of the hydrodeoxygenation reaction will be further improved by strengthening the intracrystalline diffusion and mass transfer capabilities of the molecular sieve carrier, regulating the deoxygenation capabilities, and weakening the carbon deposition of side reactions. Summary of the Invention
[0005] The present disclosure provides a hydrodeoxygenation catalyst and a preparation method and application thereof, to at least solve one of the technical problems existing in the prior art.
[0006] According to a first aspect of the present disclosure, a hydrodeoxygenation catalyst is provided, comprising an acidic zeolite support and an active bimetallic component, wherein the acidic zeolite support is a zeolite nanotube, and the active bimetallic component comprises a first metal and a second metal, wherein the first metal is Ru, and the second metal is a metal other than Ru.
[0007] In one embodiment, the second metal is one of Co, Ni, and Fe.
[0008] In one embodiment, the active bimetallic component accounts for 1 to 15 wt% of the mass of the catalyst;
[0009] The mass ratio of the first metal to the second metal in the active bimetallic component is 1:1 to 20.
[0010] According to a second aspect of the present disclosure, there is provided a method for preparing a hydrodeoxygenation catalyst, comprising:
[0011] The zeolite nanotubes, the first metal salt solution and the second metal salt solution are mixed, stirred, heated to evaporate water, dried, and then calcined in an air atmosphere at 400-650° C., and then placed in a hydrogen-inert gas mixture and reduced with hydrogen at 200-300° C. for 2-10 hours to obtain the hydrodeoxygenation catalyst.
[0012] In one embodiment, the method for preparing the zeolite nanotubes comprises:
[0013] Preparation of intermediate A: 4,4′-dihydroxybiphenyl, 1,10-dibromodecane and potassium hydroxide are added to an ethanol solution, stirred under inert gas reflux conditions, and then cooled after completion, and washed with hot ethanol and water to obtain intermediate A;
[0014] Preparation of intermediate B: intermediate A and quinuclidine are added to acetonitrile, reacted at 60-80°C under inert gas reflux, cooled after the reaction, and ether is added to precipitate the product, washed, and dried to obtain intermediate B;
[0015] Preparation of the carrier: Intermediate B is added to deionized water, followed by sodium hydroxide and hydrated aluminum sulfate, and silica gel is added dropwise with stirring. Crystallization is carried out at 140-160°C for at least 6 days. After crystallization, the mixture is centrifuged, washed with water, and dried. The mixture is then calcined in air at 400-650°C for 4-12 hours to obtain the zeolite nanotubes.
[0016] In one embodiment, in the preparation step of the intermediate A, the mass ratio of 4,4′-dihydroxybiphenyl, 1,10-dibromodecane, potassium hydroxide and ethanol is 1-2:10-14:1:70-100;
[0017] The stirring reaction under the inert gas reflux condition has a reaction temperature of 60-80° C. and a stirring time of 12-24 hours.
[0018] In one embodiment, in the preparation step of the intermediate B: the mass ratio of the intermediate A, quinuclidine and acetonitrile is 1:0.5~1:30~70; in the preparation step of the carrier: the mass ratio of the silica gel, hydrated aluminum sulfate, intermediate B, sodium hydroxide and deionized water is 2~5:0.1~0.5:1:0.2~0.8:20~50.
[0019] According to a third aspect of the present disclosure, there is provided a hydrodeoxygenation catalyst or a use of the hydrodeoxygenation catalyst obtained by the preparation method in any one of the above embodiments in preparing cycloalkanes from biomass derivatives.
[0020] In one embodiment, the hydrodeoxygenation catalyst and the biomass derivative are added to a hydrodeoxygenation solvent, mixed, and reacted under heating and hydrogen atmosphere to obtain cycloalkanes.
[0021] In one embodiment, the hydrodeoxygenation solvent is a mixture of one or more of n-decane, dodecane, tetradecane, and hexadecane;
[0022] The reaction temperature is 170-280°C, the reaction time is 0.5-4h, and the hydrogen pressure is 1-6MPa;
[0023] The biomass derivative is one or more of guaiacol, phenol, aromatic ketone, and aromatic alcohol;
[0024] The mass ratio of the hydrodeoxygenation catalyst, the biomass derivative and the hydrodeoxygenation solvent is 1:0.5-10:50-2000.
[0025] Compared with the existing technology, the advantages of this application are: 1) The hydrodeoxygenation catalyst provided by this application has the acidic sites of traditional zeolites, which ensures basic deoxygenation capacity; it also has a large specific surface area, providing sufficient points for loading active metals, while providing more contact area for reactants, thereby improving the reaction conversion rate; 2) The hydrodeoxygenation catalyst of this application has a large number of uniform and interconnected micropores and mesoporous structures, which enhances the intracrystalline mass transfer rate of reactants and reaction intermediates, improves selectivity, and reduces the occurrence of carbon deposition side reactions. 3) The preparation method of the catalyst provided by the present invention is simple and convenient. Under the premise of synthesizing a template agent with a specific structure, the traditional zeolite crystallization synthesis method is adopted, which is conducive to large-scale promotion and application.
[0026] It should be understood that the contents described in this section are not intended to identify the key or important features of the embodiments of the present disclosure, nor are they intended to limit the scope of the present disclosure. Other features of the present disclosure will become readily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings, in which several embodiments of the present disclosure are shown by way of example and not limitation, wherein:
[0028] In the drawings, the same or corresponding reference numerals denote the same or corresponding parts.
[0029] Figure 1 Transmission electron microscopy images of catalysts according to embodiments of the present disclosure are shown (wherein a) is a zeolite nanotube bundle, and b) is a zeolite nanotube;
[0030] Figure 2 Shows a scanning electron microscope image of a traditional zeolite (where a) is a ZSM-5 zeolite molecular sieve, and b) is a nanosheet zeolite);
[0031] Figure 3 shows nitrogen adsorption graphs of zeolite nanotubes, zeolite nanosheets, and ZSM-5 according to embodiments of the present disclosure;
[0032] Figure 4 shows the pore size distribution of zeolite nanotubes, zeolite nanosheets and ZSM-5 according to the embodiments of the present disclosure;
[0033] Figure 5 A graph showing the intracrystalline mass transfer rate of cyclohexane in zeolite nanotubes, zeolite nanosheets, and ZSM-5 according to an embodiment of the present disclosure is shown. DETAILED DESCRIPTION
[0034] To make the purposes, features, and advantages of the present disclosure more apparent and understandable, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present disclosure without creative work shall fall within the scope of protection of the present disclosure.
[0035] In light of the shortcomings of the prior art, the inventors of this case, after extensive research and extensive practice, were able to propose the technical solution of the present invention. The present invention utilizes a specially structured template agent to synthesize nanotubular zeolites. This not only increases the specific surface area of traditional zeolites but also introduces a uniform mesoporous structure interconnected with the micropores, enhancing the mass transfer efficiency of reactants and reaction intermediates within the zeolite crystals. Furthermore, by introducing a secondary metal into the active Ru, the dispersion of Ru particles on the support surface and their anti-agglomeration properties are enhanced, thereby improving the catalyst's lifespan. The combination of zeolite nanotubes and the bimetallic catalyst can improve the conversion rate and cycloalkane selectivity in hydrodeoxygenation reactions.
[0036] The present invention aims to provide a hydrodeoxygenation catalyst for preparing cycloalkanes from biomass derivatives, which overcomes the problems of low specific surface area and unconnected micropores and mesopores in traditional zeolite molecular sieves, and achieves high conversion efficiency, good selectivity and few side reactions.
[0037] Based on this, according to one embodiment of the present disclosure, the present invention provides a hydrodeoxygenation catalyst (referred to as "catalyst", the same below), which includes an acidic zeolite carrier and an active bimetallic component, the acidic zeolite carrier is a zeolite nanotube, and the active bimetallic component includes a first metal and a second metal, the first metal is Ru, and the second metal is a metal other than Ru.
[0038] Preferably, the second metal is one of Co, Ni and Fe.
[0039] Preferably, the zeolite nanotube has a hollow tubular structure with an inner diameter of about 3 mm. The tube wall is composed of three elements: Si, Al and O. The tube wall has zeolite characteristic micropores of about 0.5 nm. The zeolite nanotube has a large specific surface area (up to 720 m 2 / g or more), which is much higher than traditional Zsm-5 zeolite molecular sieve and zeolite nanosheets.
[0040] Preferably, the active bimetallic component accounts for 1 to 15 wt% of the mass of the catalyst; illustratively, the active bimetallic component accounts for 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt%, 13 wt%, or 15 wt% of the mass of the catalyst.
[0041] The mass ratio of the first metal to the second metal in the active bimetallic component is 1:1 to 20. For example, the mass ratio of the first metal to the second metal is 1:1, 1:3, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, or 1:20.
[0042] The hydrodeoxygenation catalyst provided herein incorporates a secondary metal into the active metal Ru to enhance the dispersion and anti-agglomeration capabilities of the Ru particles on the support surface, thereby increasing the catalyst's lifespan. Furthermore, the catalyst utilizes zeolite nanotubes as a support, increasing its surface area while introducing a uniform mesoporous structure interconnected with the micropores, enhancing the mass transfer efficiency of reactants and reaction intermediates within the zeolite crystals. This allows the catalyst to improve both the conversion rate of biomass derivatives and the selectivity for cycloalkanes during the hydrodeoxygenation reaction when used to hydrodeoxygenate cycloalkanes.
[0043] In a second aspect, the present disclosure also provides a method for preparing a hydrodeoxygenation catalyst, comprising:
[0044] The zeolite nanotubes, the first metal salt solution and the second metal salt solution are mixed, stirred, heated to evaporate water, dried, and then calcined in an air atmosphere at 400-650° C., and then placed in a hydrogen-inert gas mixture and reduced with hydrogen at 200-300° C. for 2-10 hours to obtain a hydrodeoxygenation catalyst.
[0045] For example, zeolite nanotubes, a first metal salt solution, and a second metal salt solution are mixed and stirred by an impregnation method, and then the temperature is raised to 80°C to evaporate the water, placed in an oven at 105°C to dry, calcined at 400-650°C in an air atmosphere, and then placed in a hydrogen-inert gas mixture and reduced with hydrogen at 200-300°C for 2-10 hours to obtain a hydrodeoxygenation catalyst.
[0046] For example, the first metal salt solution includes, but is not limited to, ruthenium chloride (RuCl 3 ) and ruthenium nitrate (Ru(NO 3 ) 3 ).
[0047] The second metal salt solution includes but is not limited to cobalt chloride (CoCl2), ferric chloride (FeCl3), nickel chloride (NiCl2), cobalt nitrate (Co(NO3)2), ferric nitrate (Fe(NO3)3, nickel nitrate (Ni(NO3)2), cobalt sulfate (CoSO4), ferric sulfate (Fe2(SO4)3), and nickel sulfate (NiSO4).
[0048] For example, preferably, when the zeolite nanotubes and the first / second metal salt solution are mixed, stirred, heated to evaporate the water, dried, and then calcined in an air atmosphere at 400-650°C, illustratively, the air atmosphere calcination temperature can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, and the calcination time is at least 4 hours; wherein the zeolite nanotubes and the first / second metal salt solution are mixed and stirred for 6-24 hours.
[0049] Preferably, in the hydrogen-inert gas mixture, the volume proportion of hydrogen in the mixture is 10%, and the inert gas includes but is not limited to one or more of nitrogen N2, argon Ar, and helium He.
[0050] In some embodiments, the method for preparing zeolite nanotubes comprises:
[0051] Preparation of intermediate A: 4,4′-dihydroxybiphenyl, 1,10-dibromodecane and potassium hydroxide are added to an ethanol solution, stirred under inert gas reflux conditions, and reacted. After completion, the reaction is cooled and washed with hot ethanol and water, respectively, to obtain intermediate A.
[0052] Preparation of Intermediate B: Intermediate A and quinuclidine are added to acetonitrile and refluxed at 60-80°C under an inert gas (e.g., N2, Ar, He) for at least 12 hours. After the reaction is completed, the reaction is cooled, and ether is added to precipitate the product, which is then washed with ether and dried to obtain Intermediate B.
[0053] Preparation of the carrier: Intermediate B is added to deionized water, followed by sodium hydroxide and hydrated aluminum sulfate, and silica gel is added dropwise. The mixture is stirred at room temperature and crystallized at 140-160°C for at least 6 days. After crystallization, the mixture is centrifuged, washed with water, and dried. The mixture is then calcined in air at 400-650°C for 4-12 hours to obtain zeolite nanotubes.
[0054] Preferably, in the preparation step of intermediate A, the mass ratio of 4,4′-dihydroxybiphenyl, 1,10-dibromodecane, potassium hydroxide and ethanol is 1-2:10-14:1:70-100; preferably, potassium hydroxide can also be replaced by sodium hydroxide.
[0055] Preferably, in the preparation step of intermediate A, the stirring reaction under inert gas reflux conditions is carried out at a reaction temperature of 60 to 80° C. and a stirring time of 12 to 24 hours.
[0056] Preferably, in the preparation step of the intermediate B, the mass ratio of the intermediate A, quinuclidine and acetonitrile is 1:0.5 to 1:30 to 70.
[0057] Preferably, in the carrier preparation step, the mass ratio of the silica gel, hydrated aluminum sulfate, intermediate B, sodium hydroxide, and deionized water is 2-5: 0.1-0.5: 1: 0.2-0.8: 20-50. The silica gel can be HS-30 silica gel.
[0058] Preferably, in the step of preparing the carrier, the stirring time at room temperature is 1 to 5 hours, and the crystallization temperature is 140 to 160°C. For example, the crystallization temperature may be 140°C, 150°C, or 160°C.
[0059] In a third aspect, embodiments of the present disclosure further provide use of a hydrodeoxygenation catalyst or a hydrodeoxygenation catalyst obtained by the above-described preparation method in the preparation of cycloalkanes from biomass derivatives.
[0060] In some embodiments, the hydrodeoxygenation catalyst and the biomass derivative are added to a hydrodeoxygenation solvent, mixed uniformly, and reacted under heating and hydrogen atmosphere to obtain cycloalkanes.
[0061] In some embodiments, the hydrodeoxygenation solvent is a mixture of one or more of n-decane, dodecane, tetradecane, and hexadecane;
[0062] The reaction temperature is 170-280°C, the reaction time is 0.5-4h, and the hydrogen pressure is 1-6MPa;
[0063] The biomass derivative is one or more of guaiacol, phenol, aromatic ketones, and aromatic alcohols; guaiacol, phenol, aromatic ketones, and aromatic alcohols are depolymerization products of lignin. Aromatic ketones include, but are not limited to, benzophenone. Aromatic alcohols include, but are not limited to, benzyl alcohol.
[0064] The mass ratio of the hydrodeoxygenation catalyst, the biomass derivative and the hydrodeoxygenation solvent is 1:0.5-10:50-2000.
[0065] The present application is further described in detail below with reference to the embodiments and drawings:
[0066] Example 1
[0067] A method for preparing a hydrodeoxygenation catalyst comprises:
[0068] Step (1): Add 1.6 g of 4,4′-dihydroxybiphenyl, 12.5 g of 1,10-dibromodecane and 1 g of potassium hydroxide to 100 g of ethanol solution, stir and react under nitrogen reflux (reaction temperature is 75°C, stirring for 12 hours), cool after completion, and wash with hot ethanol and water respectively to obtain intermediate A.
[0069] Step (2): 0.5 g of intermediate A and 0.35 g of quinuclidine were added to 25 g of acetonitrile and the mixture was heated to 70 °C. 、 The reaction was refluxed under nitrogen for 12 h. After the reaction was completed and cooled, ether was added to precipitate the product, which was washed with ether and dried to obtain intermediate B.
[0070] Step (3): 0.113 g of Intermediate B was added to 4.45 g of deionized water, followed by 0.067 g of sodium hydroxide, 0.027 g of hydrated aluminum sulfate, and 0.5 g of HS-30 silica gel dropwise. The mixture was stirred at room temperature for 3 hours and then crystallized in a polytetrafluoroethylene autoclave at 150°C for 7 days. After crystallization, the mixture was centrifuged, washed with water, and dried. The mixture was then calcined in air at 550°C for 6 hours to obtain zeolite nanotubes.
[0071] Step (4): The first metal salt solution (i.e., RuCl3) and the second metal salt solution (i.e., CoCl2) were mixed with the zeolite nanotubes and stirred for 10 hours. The mixture was then heated to 80°C to evaporate the water and dried in an oven at 105°C. The mixture was then calcined at 550°C in air for 4 hours and then reduced in a 10% hydrogen-nitrogen mixture at 250°C for 4 hours to obtain a Ru-Co bimetallic catalyst with a 10% loading, wherein the mass ratio of Ru to Co was 1:15.
[0072] Application of a hydrodeoxygenation catalyst in the preparation of cycloalkanes from biomass derivatives:
[0073] The method comprises adding 20 mg of the catalyst of step (4) and 20 mg of guaiacol to 20 g of n-dodecane solution, the hydrogen pressure in the reactor being 2 MPa, the temperature being 240° C., and reacting for 2 hours, the conversion rate of guaiacol being 99.9%, and the selectivity of cyclohexane being 99%.
[0074] Example 2
[0075] A method for preparing a hydrodeoxygenation catalyst comprises:
[0076] Step (1): Add 1 g of 4,4′-dihydroxybiphenyl, 10 g of 1,10-dibromodecane and 1 g of potassium hydroxide to 70 g of ethanol solution, stir and react under nitrogen reflux (reaction temperature is 60°C, stirring for 12 hours), cool and wash with hot ethanol and water respectively to obtain intermediate A.
[0077] Step (2): 1 g of intermediate A and 0.5 g of quinuclidine were added to 30 g of acetonitrile, and the mixture was refluxed at 60° C. under nitrogen for 12 h. After the reaction was completed and cooled, ether was added to precipitate the product, which was washed with ether and dried to obtain intermediate B.
[0078] Step (3): 1 g of intermediate B was added to 20 g of deionized water, followed by 0.2 g of sodium hydroxide, 0.1 g of hydrated aluminum sulfate, and 2 g of HS-30 silica gel, added dropwise. The mixture was stirred at room temperature for 3 hours and then crystallized in a polytetrafluoroethylene autoclave at 150°C for 7 days. After crystallization, the mixture was centrifuged, washed with water, and dried. The mixture was then calcined in air at 550°C for 6 hours to obtain zeolite nanotubes.
[0079] Step (4): The first metal salt solution (i.e., RuCl3) and the second metal salt solution (i.e., CoCl2) were mixed with the zeolite nanotubes and stirred for 10 hours. The mixture was then heated to 80°C to evaporate the water and dried in an oven at 105°C. The mixture was then calcined at 550°C in air for 4 hours and then reduced in a 10% hydrogen-nitrogen mixture at 250°C for 4 hours to obtain a Ru-Co bimetallic catalyst with a 1% loading, wherein the mass ratio of Ru to Co was 1:10.
[0080] Application of a hydrodeoxygenation catalyst in the preparation of cycloalkanes from biomass derivatives:
[0081] The method comprises the following steps: adding 20 mg of the catalyst of step (4) and 10 mg of guaiacol to 1 g of n-dodecane solution; setting the hydrogen pressure of the reactor to 1 MPa and the temperature to 280° C.; and reacting for 0.5 hours; the conversion rate of guaiacol is 90%; and the selectivity of cyclohexane is 70%.
[0082] Example 3
[0083] A method for preparing a hydrodeoxygenation catalyst comprises:
[0084] Step (1): Add 2 g of 4,4′-dihydroxybiphenyl, 14 g of 1,10-dibromodecane and 1 g of potassium hydroxide to 100 g of ethanol solution, stir and react under nitrogen reflux (reaction temperature is 80°C, stirring for 12 hours), cool and wash with hot ethanol and water respectively to obtain intermediate A.
[0085] Step (2): 1 g of intermediate A and 1 g of quinuclidine were added to 70 g of acetonitrile, and the mixture was refluxed at 80° C. under nitrogen for 12 h. After the reaction was completed and cooled, ether was added to precipitate the product, which was washed with ether and dried to obtain intermediate B.
[0086] Step (3): 1 g of intermediate B was added to 50 g of deionized water, followed by 0.8 g of sodium hydroxide, 0.5 g of hydrated aluminum sulfate, and 5 g of HS-30 silica gel, added dropwise. The mixture was stirred at room temperature for 3 hours and then crystallized in a polytetrafluoroethylene autoclave at 150°C for 7 days. After crystallization, the mixture was centrifuged, washed with water, and dried. The mixture was then calcined in air at 550°C for 6 hours to obtain zeolite nanotubes.
[0087] Step (4): The first metal salt solution, the second metal salt solution, and the zeolite nanotubes were mixed and stirred for 10 hours, then heated to 80°C to evaporate the water and dried in an oven at 105°C. The mixture was then calcined at 550°C in air for 4 hours, and then reduced in a 10% hydrogen-nitrogen mixture at 250°C for 4 hours to obtain a Ru-Co bimetallic catalyst with a 15% loading, wherein the mass ratio of Ru to Co was 1:20.
[0088] Application of a hydrodeoxygenation catalyst in the preparation of cycloalkanes from biomass derivatives:
[0089] The method comprises adding 20 mg of the catalyst of step (4) and 200 mg of guaiacol to 40 g of n-dodecane solution, setting the reactor hydrogen pressure to 6 MPa and the temperature to 170° C., and reacting for 4 hours. The conversion rate of guaiacol is 20%, and the selectivity of cyclohexane is 60%.
[0090] Example 4
[0091] A method for preparing a hydrodeoxygenation catalyst comprises:
[0092] Step (1): 1.6 g of 4,4′-dihydroxybiphenyl, 12.5 g of 1,10-dibromodecane and 1 g of potassium hydroxide were added to 100 g of ethanol solution, and the mixture was stirred under nitrogen reflux (reaction temperature was 65° C., and stirring was performed for 12 h). After cooling, the mixture was washed with hot ethanol and water, respectively, to obtain intermediate A.
[0093] Step (2): 0.5 g of intermediate A and 0.35 g of quinuclidine were added to 20 g of acetonitrile, and the mixture was refluxed at 65° C. under nitrogen for 12 h. After the reaction was completed and cooled, ether was added to precipitate the product, which was washed with ether and dried to obtain intermediate B.
[0094] Step (3): 0.113 g of Intermediate B was added to 4.45 g of deionized water, followed by 0.067 g of sodium hydroxide, 0.027 g of hydrated aluminum sulfate, and 0.5 g of HS-30 silica gel dropwise. The mixture was stirred at room temperature for 3 hours and then crystallized in a polytetrafluoroethylene autoclave at 150°C for 7 days. After crystallization, the mixture was centrifuged, washed with water, and dried. The mixture was then calcined in air at 550°C for 6 hours to obtain zeolite nanotubes.
[0095] Step (4): The first metal salt solution (i.e., RuCl3) and the second metal salt solution (i.e., NiCl2) were mixed with the zeolite nanotubes and stirred for 10 hours. The mixture was then heated to 80°C to evaporate the water and dried in an oven at 105°C. The mixture was calcined at 550°C in air for 4 hours and then reduced in a 10% hydrogen-nitrogen mixture at 250°C for 4 hours to obtain a Ru-Ni bimetallic catalyst with a loading of 5%, wherein the mass ratio of Ru to Ni was 1:5.
[0096] Application of a hydrodeoxygenation catalyst in the preparation of cycloalkanes from biomass derivatives:
[0097] The method comprises adding 20 mg of the catalyst of step (4) and 20 mg of phenol to 17 g of n-decane, setting the hydrogen pressure of the reactor to 1 MPa and the temperature to 190° C., and reacting for 2 hours. The conversion rate of phenol is 99.9%, and the selectivity of cyclohexane is 95%.
[0098] Example 5
[0099] A method for preparing a hydrodeoxygenation catalyst comprises:
[0100] Step (1): 1.6 g of 4,4′-dihydroxybiphenyl, 12.5 g of 1,10-dibromodecane and 1 g of potassium hydroxide were added to 100 g of ethanol solution, and the mixture was stirred under nitrogen reflux (reaction temperature was 80° C., and stirring was performed for 12 h). After cooling, the mixture was washed with hot ethanol and water, respectively, to obtain intermediate A.
[0101] Step (2): 0.5 g of intermediate A and 0.35 g of quinuclidine were added to 20 g of acetonitrile, and the mixture was refluxed at 80° C. under nitrogen for 12 h. After the reaction was completed and cooled, ether was added to precipitate the product, which was washed with ether and dried to obtain intermediate B.
[0102] Step (3): 0.113 g of Intermediate B was added to 4.45 g of deionized water, followed by 0.067 g of sodium hydroxide, 0.027 g of hydrated aluminum sulfate, and 0.5 g of HS-30 silica gel dropwise. The mixture was stirred at room temperature for 3 hours and then crystallized in a polytetrafluoroethylene autoclave at 150°C for 7 days. After crystallization, the mixture was centrifuged, washed with water, and dried. The mixture was then calcined in air at 550°C for 6 hours to obtain zeolite nanotubes.
[0103] Step (4): The first metal salt solution (i.e., RuCl3) and the second metal salt solution (i.e., FeCl3) were mixed with the zeolite nanotubes and stirred for 10 hours. The mixture was then heated to 80°C to evaporate the water and dried in an oven at 105°C. The mixture was calcined at 550°C in air for 4 hours and then reduced in a 10% hydrogen-nitrogen mixture at 250°C for 4 hours to obtain a Ru-Fe bimetallic catalyst with an 8% loading, wherein the mass ratio of Ru to Fe was 1:12.
[0104] Application of a hydrodeoxygenation catalyst in the preparation of cycloalkanes from biomass derivatives:
[0105] The method comprises adding 20 mg of the catalyst of step (4) and 30 mg of the aromatic ketone to 17 g of n-tetradecane, setting the reactor hydrogen pressure to 3 MPa and the temperature to 210° C., and reacting for 1.5 hours. The conversion rate of benzophenone is 98%, and the selectivity of cyclohexane is 85%.
[0106] Example 6
[0107] A method for preparing a hydrodeoxygenation catalyst comprises:
[0108] Step (1): 1.6 g of 4,4′-dihydroxybiphenyl, 12.5 g of 1,10-dibromodecane and 1 g of potassium hydroxide were added to 100 g of ethanol solution, and the mixture was stirred under nitrogen reflux (reaction temperature was 70° C., and stirring was performed for 12 h). After cooling, the mixture was washed with hot ethanol and water, respectively, to obtain intermediate A.
[0109] Step (2): 0.5 g of intermediate A and 0.35 g of quinuclidine were added to 30 g of acetonitrile, and the mixture was refluxed at 75° C. under nitrogen for 12 h. After the reaction was completed and cooled, ether was added to precipitate the product, which was washed with ether and dried to obtain intermediate B.
[0110] Step (3): 0.113 g of Intermediate B was added to 4.45 g of deionized water, followed by 0.067 g of sodium hydroxide, 0.027 g of hydrated aluminum sulfate, and 0.5 g of HS-30 silica gel dropwise. The mixture was stirred at room temperature for 3 hours and then crystallized in a polytetrafluoroethylene autoclave at 150°C for 7 days. After crystallization, the mixture was centrifuged, washed with water, and dried. The mixture was then calcined in air at 550°C for 6 hours to obtain zeolite nanotubes.
[0111] Step (4): The first metal salt solution (i.e., RuCl3) and the second metal salt solution (i.e., FeCl3) were mixed with the zeolite nanotubes and stirred for 10 hours. The mixture was then heated to 80°C to evaporate the water and dried in an oven at 105°C. The mixture was calcined at 550°C in air for 4 hours and then reduced in a 10% hydrogen-nitrogen mixture at 250°C for 4 hours to obtain a Ru-Fe bimetallic catalyst with an 8% loading, wherein the mass ratio of Ru to Fe was 1:12.
[0112] Application of a hydrodeoxygenation catalyst in the preparation of cycloalkanes from biomass derivatives:
[0113] The method comprises adding 20 mg of the catalyst of step (4) and 20 mg of aromatic alcohol to 20 g of n-hexadecane, setting the reactor hydrogen pressure at 2 MPa and the temperature at 240° C. for 2 hours, wherein the conversion rate of benzyl alcohol is 97% and the selectivity of cyclohexane is 90%.
[0114] Comparative Example 1
[0115] This comparative example 1 is a comparative example of Example 1
[0116] The catalyst preparation method and the cycloalkane preparation method of this comparative example 1 are substantially the same as those of Example 1, except that: the comparative example 1 uses a conventional ZSM-5 zeolite molecular sieve for metal loading ( Figure 2 a) A Ru-Co bimetallic catalyst with a 10% loading was obtained, wherein the mass ratio of Ru to Co was 1:15. Cycloalkanes were prepared under the same conditions, and the evaluation results showed a guaiacol conversion of 95% and a cyclohexane selectivity of 94%.
[0117] Comparative Example 2
[0118] This comparative example 2 is a comparative example of Example 1
[0119] The catalyst preparation method and cycloalkane preparation method of this comparative example 2 are substantially the same as those of Example 1, except that: the comparative example 1 uses zeolite nanosheets for metal loading ( Figure 2 b) A Ru-Co bimetallic catalyst with a 10% loading was obtained, wherein the mass ratio of Ru to Co was 1:15. Cycloalkanes were prepared under the same conditions, and the evaluation results showed a guaiacol conversion of 97% and a cyclohexane selectivity of 96%.
[0120] Comparative Example 3
[0121] This comparative example 3 is a comparative example of Example 1
[0122] The catalyst preparation method and cycloalkane preparation method of this comparative example 3 are substantially the same as those of Example 1, except that no metal salt solution is added in step (4). Cycloalkane preparation is carried out under the same conditions. Evaluation results show that the guaiacol conversion rate is 80% and the cyclohexane selectivity is 10%.
[0123] Comparative Example 4
[0124] This comparative example 4 is a comparative example of Example 1
[0125] The catalyst preparation method and cycloalkane preparation method of this comparative example 4 are substantially the same as those of Example 1, except that in step (4), only single metal Ru loading is performed to obtain a catalyst with a Ru metal loading of 10%. Cycloalkane preparation is performed under the same conditions. Evaluation results show that the guaiacol conversion rate is 97% and the cyclohexane selectivity is 98%.
[0126] Characterization and testing
[0127] 1), the catalyst prepared in Example 1 was tested by transmission electron microscopy, and the transmission electron microscopy image was as follows Figure 1 As shown. Figure 1 It can be seen that the prepared zeolite nanotubes have a typical tubular structure and are distributed in bundles. The diameter of a single tube is about 4 nm, and the wall thickness between tubes is very thin, showing a one-dimensional structural feature.
[0128] In addition, the present application also carried out scanning electron microscopy on the traditional zeolite, e.g. Figure 2 As shown, Figure 2 a is a scanning electron microscope image of ZSM-5 zeolite molecular sieve, Figure 2 b is a scanning electron microscope image of zeolite nanosheets. Figure 2 It can be seen that zeolite nanosheets have a typical sheet structure, showing two-dimensional structural characteristics, with sheets stacked in a staggered manner. ZSM-5 has a typical block structure, showing three-dimensional structural characteristics. Figure 1 The zeolite nanotubes show significant differences in microscopic morphology.
[0129] 2) The zeolite nanotubes prepared in Example 1, as well as conventional zeolite nanosheets and ZSM-5 zeolite molecular sieves were subjected to nitrogen adsorption tests. The results are shown in FIG. Figure 3 shown.
[0130] from Figure 3 It can be seen that the adsorption of nitrogen by the zeolite nanotubes prepared in Example 1 is much greater than that by the zeolite nanosheets and ZSM-5 zeolite molecular sieve. The specific surface area of the nanotubes obtained by BET calculation is as high as 720 m 2 / g, which is higher than that of zeolite nanosheets and ZSM-5.
[0131] 3) The pore size distribution of the zeolite nanotubes prepared in Example 1, as well as conventional zeolite nanosheets and ZSM-5 zeolite molecular sieves, was tested. The results are shown in FIG. Figure 4 shown.
[0132] from Figure 4 It can be seen that zeolite nanotubes, zeolite nanosheets and ZSM-5 all have micropore structures below 1 nm, but the mesopore distribution of zeolite nanotubes is much higher than that of zeolite nanosheets and ZSM-5, and the distribution is more concentrated.
[0133] 4), the intracrystalline mass transfer rate of cycloalkanes (specifically cyclohexane) in zeolite nanotubes, traditional zeolite nanosheets and ZSM-5 zeolite molecular sieves was tested, and the results are as follows Figure 5 shown.
[0134] from Figure 5 As can be seen from the figure, the order of intracrystalline mass transfer rates of cycloalkanes within the three zeolite molecular sieve supports is zeolite nanotubes, zeolite nanosheets, and ZSM-5, from fastest to slowest. Zeolite nanotubes exhibit a much higher intracrystalline mass transfer rate than the other two supports. This is closely related to the high specific surface area and uniformly interconnected micro-mesoporous structure of zeolite nanotubes. The high intracrystalline mass transfer rate of zeolite nanotubes to the product facilitates improved conversion and selectivity in catalytic reactions.
[0135] It should be understood that the various forms of the processes shown above can be used to reorder, add, or delete steps. For example, the steps described in this disclosure can be performed in parallel, sequentially, or in a different order, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved. This is not a limitation herein.
[0136] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features being referred to. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one such feature. Throughout the present disclosure, "plurality" means two or more, unless otherwise specifically defined.
[0137] The above description is merely a specific embodiment of the present disclosure, but the scope of protection of the present disclosure is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this disclosure should be included in the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure should be based on the scope of protection of the claims.
Claims
1. A hydrodeoxygenation catalyst, characterized in that: The catalyst comprises an acidic zeolite carrier and an active bimetallic component, wherein the acidic zeolite carrier is a zeolite nanotube, and the active bimetallic component comprises a first metal and a second metal, wherein the first metal is Ru, and the second metal is a metal other than Ru.
2. The hydrodeoxygenation catalyst according to claim 1, characterized in that: The second metal is one of Co, Ni and Fe.
3. The hydrodeoxygenation catalyst according to claim 1, characterized in that: The active bimetallic component accounts for 1 to 15 wt% of the mass of the catalyst; The mass ratio of the first metal to the second metal in the active bimetallic component is 1:1-20.
4. The method for preparing the hydrodeoxygenation catalyst according to any one of claims 1 to 3, characterized in that: include: The zeolite nanotubes, the first metal salt solution and the second metal salt solution are mixed, stirred, heated to evaporate water, dried, and then calcined in an air atmosphere at 400-650° C., and then placed in a hydrogen-inert gas mixture and reduced with hydrogen at 200-300° C. for 2-10 hours to obtain the hydrodeoxygenation catalyst.
5. The preparation method according to claim 4, characterized in that: The preparation method of the zeolite nanotubes comprises: Preparation of intermediate A: 4,4′-dihydroxybiphenyl, 1,10-dibromodecane and potassium hydroxide are added to an ethanol solution, stirred under inert gas reflux conditions, cooled after completion, and washed with hot ethanol and water to obtain intermediate A; Preparation of intermediate B: intermediate A and quinuclidine are added to acetonitrile, reacted at a temperature of 60-80°C and reflux of inert gas, cooled after the reaction, ether is added to precipitate the product, washed, and dried to obtain intermediate B; Preparation of the carrier: Add intermediate B to deionized water, then add sodium hydroxide and hydrated aluminum sulfate, add silica gel dropwise, stir, and crystallize at 140-160°C for at least 6 days; after crystallization, centrifuge, wash with water, and dry; then calcine in air at 400-650°C for 4-12 hours to obtain the zeolite nanotubes.
6. The preparation method according to claim 5, characterized in that: In the preparation step of the intermediate A, the mass ratio of 4,4′-dihydroxybiphenyl, 1,10-dibromodecane, potassium hydroxide and ethanol is 1-2:10-14:1:70-100; The stirring reaction under the inert gas reflux condition has a reaction temperature of 60 to 80° C. and a stirring time of 12 to 24 hours.
7. The preparation method according to claim 5, characterized in that: In the preparation step of the intermediate B: the mass ratio of the intermediate A, quinuclidine and acetonitrile is 1:0.5 to 1:30 to 70; In the preparation step of the carrier: the mass ratio of the silica gel, hydrated aluminum sulfate, intermediate B, sodium hydroxide and deionized water is 2-5: 0.1-0.5: 1: 0.2-0.8: 20-50.
8. Use of the hydrodeoxygenation catalyst according to any one of claims 1 to 3 or the hydrodeoxygenation catalyst obtained by the preparation method according to any one of claims 4 to 7 in the preparation of cycloalkanes from biomass derivatives.
9. The use according to claim 8, characterized in that: The hydrodeoxygenation catalyst and the biomass derivative are added into a hydrodeoxygenation solvent, mixed, and reacted under heating and hydrogen atmosphere conditions to obtain cycloalkanes.
10. The use according to claim 9, characterized in that: The hydrodeoxygenation solvent is a mixture of one or more of n-decane, dodecane, tetradecane and hexadecane; The reaction temperature is 170-280°C, the reaction time is 0.5-4h, and the hydrogen pressure is 1-6MPa; The biomass derivative is one or more of guaiacol, phenol, aromatic ketone, and aromatic alcohol; The mass ratio of the hydrodeoxygenation catalyst, the biomass derivative and the hydrodeoxygenation solvent is 1:0.5-10:50-2000.
Citation Information
Patent Citations
Preparation method of hierarchical porous ZSM-5 molecular sieve with 90-degree interactive inter-growth
CN108439429A
Preparation of metal-in-hollow-zeolite-based catalyst for selective benzene alkylation
CN110621400A
Hydrodeoxygenation catalyst, application thereof and preparation method of cyclohexane
CN112090443A
Nanostructured catalyst for hydrodeoxygenation of aromatic oxygen-containing components of biooil
RU2797423C1
Hydrodeoxygenation of lignin to hydrocarbons using bimetallic catalysts
US20190233743A1